Improving Children's Artistic Skills through Beautiful Bottle Learning Media for Group B in Makkah at RA Al Hidayah Guppi I Bedali - Mahmudah (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to improve children's artistic abilities through the use of the Beautiful Bottle learning media in group B Makkah children at RA Al Hidayah GUPPI I Bedali. The background of the study began with the low interest of children in participating in artistic activities, especially singing and learning about music. This condition encouraged the researcher to use the Beautiful Bottle media as an educational prop made from eight used glass beverage bottles that were attractively decorated and filled with water at different heights to produce a variety of tones. The research method used was classroom action research (CAR) which was carried out in four cycles, with 20 children as research subjects. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed a significant increase in children's artistic abilities, both in terms of recognizing the sound of notes, following the rhythm, and enthusiasm in learning activities. In addition to the artistic aspect, the Beautiful Bottle media also contributed to developing children's cognitive, social, motor, and language aspects. Children appeared more active, creative, and able to collaborate in simple musical activities. Thus, the use of the Beautiful Bottle media has proven effective as an innovation in art learning for early childhood, and can be used as an alternative for teachers in creating a fun and meaningful learning atmosphere.